If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4xy + 2x + 6y + 3 = 0 Reorder the terms: 3 + 2x + 4xy + 6y = 0 Solving 3 + 2x + 4xy + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 2x + 4xy + -3 + 6y = 0 + -3 Reorder the terms: 3 + -3 + 2x + 4xy + 6y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x + 4xy + 6y = 0 + -3 2x + 4xy + 6y = 0 + -3 Combine like terms: 0 + -3 = -3 2x + 4xy + 6y = -3 Add '-6y' to each side of the equation. 2x + 4xy + 6y + -6y = -3 + -6y Combine like terms: 6y + -6y = 0 2x + 4xy + 0 = -3 + -6y 2x + 4xy = -3 + -6y Reorder the terms: 3 + 2x + 4xy + 6y = -3 + -6y + 3 + 6y Reorder the terms: 3 + 2x + 4xy + 6y = -3 + 3 + -6y + 6y Combine like terms: -3 + 3 = 0 3 + 2x + 4xy + 6y = 0 + -6y + 6y 3 + 2x + 4xy + 6y = -6y + 6y Combine like terms: -6y + 6y = 0 3 + 2x + 4xy + 6y = 0 The solution to this equation could not be determined.
| (y-5)-(y+7)=8y | | X-26=4 | | 4q=92 | | 3t-3=9+9t | | 5c+12=7c+11.84 | | 10x+x^2=84 | | -3x-30x-75=0 | | -10y^2-4(5y^2-8)+6y= | | -x^2-4x=-47 | | -5+8(x-3)=17x+2-9x | | -x^2-4x= | | 18=0.2x+5 | | -3(-7-6n)=-11+2(4+5n) | | 52+14m=318 | | -9+10=m-9 | | 10x-4=6x+2 | | 7x+10=-60-7x | | 7x+10=-60-7x | | 2m+14-5(m-1)=9m-(5m-4)-8m+9 | | (6+x)*(10+x)=144 | | m^2-14+49=0 | | 33n-195=234 | | mx^2+(2m+3)x+(m-1)=0 | | -9m+51-9(m-3)=3m-(4m-4)-2m+1 | | 7x+17=52 | | 8+2n=20 | | 7+3n=19 | | 2y-6=5x+8 | | 9(r+8)= | | 24=x-36 | | 3t+9t=-110 | | 2x+x-6=90 |